(untitled) - Masters, Gilbert M. (Hoboken, NJ, 2004)
This is a comprehensive textbook for the new trend of distributed power generation systems and renewable energy sources in electric power systems. It covers the complete range of topics from fundamental concepts to major technologies as well as advanced topics for power consumers.
Keywords: Hệ thống điện,Electric power systems; Bảo tồn năng lượng,Energy conservation